Origin and functional differentiation of (E)-β-ocimene synthases reflect the expansion of monoterpenes in angiosperms. (28th July 2020) - Ding, Guangyu; Zhang, Shaoyu; Ma, Bi; Liang, Jiubo; Li, Han; Luo, Yiwei; He, Ningjia
Abstract : Genetic, phylogenetic, and biochemical analyses reveal the origin and evolution of ( E )-β-ocimene synthases from biochemical and evolutionary biology perspectives, and explain the expansion of monoterpenes in angiosperms. Abstract: The acquisition of new metabolic activities is a major force driving evolution. We explored, from the perspectives of gene family expansion and the evolutionary adaptability of proteins, how new functions have arisen in which terpene synthases diverged. Monoterpenoids are diverse natural compounds that can be divided into cyclic and acyclic skeleton forms according to their chemical structure. We demonstrate, through phylogenetic reconstructions and genome synteny analyses, that the ( E )-β-ocimene synthases, which are acyclic monoterpene synthases (mTPSs), appear to have arisen several times in independent lineages during plant evolution. Bioinformatics analyses and classical mutation experiments identified four sites (I388, F420, S446, and F485) playing important roles in the neofunctionalization of mTPSs. Incubation of neryl diphosphate with Salvia officinalis 1, 8-cineole synthase (SCS) and mutated proteins show that these four sites obstruct the isomerization of geranyl diphosphate. Quantum mechanical/molecular mechanical molecular dynamics simulations of models of SCS, SCS Y420F/I446S, and SCS N338I/Y420F/I446S/L485F with ( 3R )-linalyl diphosphate suggest that mutations changed the configuration of the intermediate to obtain new activities. These results provide new perspectives on the evolution of mTPSs, explain the convergent evolution of ( E )-β-ocimene synthases at the molecular level, and identify key residues to control the specificity of engineered mTPSs.